Deuda bancaria versus deuda comercial y tiempo de resolución del concurso - Inmaculada Aguiar Díaz; María Victoria Ruiz Mallorquí (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2015)
– This work has the aim of analyzing the influence of bank and trade debt in the duration of the process of bankruptcy in Spain. To that end, a sample of 567 firms, that fill in bankruptcy between 2004 and 2009, is used. The results show a different behavior between banks and trade creditors, considering the level of their debt and the type of bankruptcy resolution. Thus, whereas the former allow a lengthening of the process, the latter try to reduce it. In addition, those results remain in the sample of firms that liquidate, whereas in the firms that reach an agreement, only the attitude of trade creditors is relevant, who besides, have a different behavior depending on the type of resolution.
Keywords: G21; G33; K22; 330; Bankruptcy; Bank debt; Trade debt; Time of bankruptcy